ANALISIS TARIKAN PASAR BABADAN UNGARAN KAB. SEMARANG DAN KINERJA LALU LINTAS JALAN SEKITAR - Putmadiat Rochhanif; Raymon Raymon; Bagus Hario Setiadji; Wahyudi Kushardjoko (Jurnal Karya Teknik Sipil, 2013)
Market as an activity zone trips towing zones. Babadan Market located at Jalan Sudirman, where the market activity zone Babadan Ungaran generate visitor attraction and trip generation in the form of a private car and public transport resulting in congestion. This condition should be corrected in order to get the convenience of shopping at Babadan traditional market and smooth flow of traffic on Soedirman street. For that to know the amount of travel due to the existence of  Babadan traditional market. Therefore, we evaluated to determine the performance of Jend. Soedirman street and Raya Baya street with calculations based on the degree of saturation on traffic survey and evaluation of the resistance that occur on the road. Evaluation results show the degree of saturation at Jend. Soedirman street  ≥ 0.75 so that its necessary treatment. Whereas at Raya Baya street ≤ 0.75 it is still in a safe condition. Planning by reducing the resistance, optimizing pedestrian bridge, reviewing u - turn, and the control of bus bay.